Indigenous spirits and global aspirations in a southeast Asian borderland Timor-Leste's Oecussi enclave - Rose, Michael (Amsterdam University Press, 2020)
Over the past 40 years, life in Timor-Leste has changed radically. Before 1975 most of the population lived in highland villages, spoke local languages, and rarely used money. Today many have moved to peri-urban lowland settlements, and even those whose lives remain dominated by customary ways understand that those of their children will not. For the Atoni Pah Meto of Timor-Leste's remote Oecussi Enclave, the world was neatly divided into two distinct categories: the meto (indigenous), and the kase (foreign). Now matters are less clear; the good things of the globalised world are pursued not through rejecting the meto ways of the village, or collapsing them into the kase, but through continual crossing between them. In this way, the people of Oecussi are able to identify in the struggles of lowland life, the comforting and often decisive presence of familiar highland spirits.